Modified high-performance fiber braided fabric and preparation method and application thereof
By mixing nanomaterials with high-performance fiber monomers during the spinning stage, modified fibers are prepared and woven into modified high-performance fiber fabrics, solving the problem of difficulty in achieving both impact resistance and electromagnetic shielding performance in existing technologies, and realizing material stability and efficient production.
Patent Information
- Application Number
- CN202511240478.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-01
- Publication Date
- 2025-12-09
AI Technical Summary
Existing technologies struggle to simultaneously achieve both impact resistance and electromagnetic shielding properties in fiber materials. Furthermore, existing methods suffer from issues such as easy coating and plating peeling, poor flexibility, weak interfacial adhesion, and low production efficiency.
In the spinning stage, nanomaterials are mixed with high-performance fiber monomers to prepare modified fibers through spinning technology, and then a braiding process is used to form modified high-performance fiber woven fabrics. The nanomaterials are arranged axially inside the fibers to form a conductive network to improve electromagnetic shielding performance.
It achieves uniform distribution of nanomaterials inside the fiber, improves impact resistance and electromagnetic shielding effect, maintains the lightweight properties of the fiber, and avoids the problem of coating and plating peeling. It is suitable for fields such as protective equipment, composite armor, consumer electronics and smart textiles.
Smart Images

Figure CN121087672A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a fiber braided fabric, specifically to a modified high-performance fiber braided fabric that integrates impact resistance and electromagnetic shielding functions, its preparation method, and its application, belonging to the field of materials science and technology. Background Technology
[0002] In this era of rapid technological advancement, the widespread use of electronic devices has led to increasingly complex electromagnetic environments. Electromagnetic radiation not only interferes with the normal operation of electronic equipment but also poses potential threats to human health. Meanwhile, in numerous fields such as aerospace, defense, and transportation, materials face various impact loads, placing stringent demands on their impact resistance. In the low-altitude economy, low-altitude aircraft are susceptible to external environmental factors during operation, such as airflow disturbances, bird strikes, collisions with small drones, and debris encountered during flight. Therefore, the impact resistance of materials determines the reliability and safety of the aircraft structure. Furthermore, low-altitude aircraft rely heavily on wireless communication, navigation, and electronic control systems, making electromagnetic shielding materials crucial for ensuring stable operation. Therefore, developing a material that combines impact resistance and electromagnetic shielding is of paramount practical significance. Such a material can provide reliable physical protection for personnel and equipment while ensuring stable equipment operation, effectively improving the safety and reliability of the system.
[0003] Existing fiber-woven fabrics often struggle to simultaneously possess both impact resistance and electromagnetic shielding properties. Modifying fibers or fabrics to impart additional functionalities is a common approach. Nanomaterials such as carbon nanotubes and graphene possess excellent mechanical, thermal, electrical, and chemical properties, demonstrating unique advantages in the modification of high-performance fibers and fabrics. As additives, they can effectively enhance the overall performance of high-performance fibers (such as aramid, PBO, and UHMWPE), providing better impact resistance, electromagnetic shielding capabilities, conductivity, and high-temperature resistance. Existing literature reports that even small amounts of these additives can significantly improve the mechanical and electromagnetic shielding properties of fibers and other materials. Carbon nanotubes and graphene can form nano-reinforcing networks within or on the surface of fibers, effectively absorbing and dispersing impact energy, thus improving the material's impact resistance. Simultaneously, they can form highly efficient conductive networks, creating conductive pathways within the fibers, enhancing conductivity, and reflecting, absorbing, and scattering electromagnetic waves, resulting in modified fibers with excellent electromagnetic shielding capabilities.
[0004] Currently, some patents modify fibers or woven fabrics by directly coating them with nanomaterials such as graphene, while others involve immersing fibers or woven fabrics directly in dispersions of graphene or similar materials. Other patents apply coatings or platings to the surface of high-performance fiber woven fabrics to enhance conductivity and electromagnetic shielding performance. Still other patents achieve impact resistance and electromagnetic shielding through three-dimensional fabrics and polymer foam filling, such as using conductive yarns woven into a three-dimensional woven structure and then filling it with nanoparticles. Some patents propose methods for growing nanowires on fabric surfaces to improve the fabric's ballistic performance while simultaneously imparting electromagnetic shielding and UV resistance. Specifically, by growing zinc oxide nanowires on filament yarn woven fabrics, the fiber surface is roughened, thereby increasing the friction between the yarns and enhancing ballistic performance. The treated fabrics achieve shielding effects of 59% in the high-frequency band and 45% in the low-frequency band.
[0005] However, the above methods have the following drawbacks: 1) High-performance fibers are woven into special woven structures, and a metal layer is coated or plated on the surface of the woven fabric. Although this method is relatively simple and easy to implement, and the woven fabric has good impact resistance and shielding performance, the coating and plating are prone to peeling off during actual use, resulting in a limited service life and a decrease in impact resistance and shielding effect. Moreover, the process of metal plating and coating textiles limits the application of the material in extreme environments; 2) Growing nanowires on the surface of fibers or woven fabrics requires specific catalysts and deposition environments, making it difficult to apply on a large scale on ordinary growth lines; 3) Introducing conductive yarns such as metal wires into the woven structure results in woven fabrics with poor flexibility and heavy weight, affecting flexibility; 4) Using nanomaterials to coat high-performance fibers can improve conductivity without sacrificing mechanical properties, achieving a more uniform electromagnetic shielding effect and enhancing impact resistance. However, the interfacial bonding is not high, the durability is poor, and the production efficiency is low. Summary of the Invention
[0006] The main objective of this invention is to provide a modified high-performance fiber woven fabric that integrates impact resistance and electromagnetic shielding functions, as well as its preparation method, to overcome the shortcomings of the prior art.
[0007] Another object of the present invention is to provide applications of the modified high-performance fiber woven fabric.
[0008] To achieve the aforementioned objectives, the technical solution adopted by this invention includes:
[0009] This invention provides a method for preparing modified high-performance fiber woven fabric, comprising:
[0010] Nanomaterials used as functional fillers are mixed with high-performance fiber monomers to uniformly disperse the nanomaterials in the high-performance fiber monomers, resulting in a mixture.
[0011] Using the mixture as a spinning solution, modified fibers are prepared by spinning technology, wherein nanomaterials are arranged axially inside the modified fibers.
[0012] The modified fibers are woven using a weaving process to obtain a modified high-performance fiber woven fabric.
[0013] In some embodiments, the nanomaterial is a chemically functionalized nanomaterial. The chemical functionalization includes at least one of carboxylation and amination.
[0014] The present invention also provides modified high-performance fiber woven fabrics prepared by the aforementioned preparation method.
[0015] This invention also provides a composite material comprising: a resin matrix material and the modified high-performance fiber woven fabric.
[0016] This invention also provides applications of the modified high-performance fiber woven fabric or composite material in fields such as protective equipment, composite armor, consumer electronics, low-altitude economy, or smart textiles.
[0017] Compared with the prior art, the beneficial effects of the present invention include at least the following:
[0018] 1) This invention introduces nanomaterials during the spinning stage, which are then uniformly dispersed inside the fiber to enhance the fiber's strength, toughness, elongation at break, and impact resistance. The braided structure design can further absorb impact energy and improve the overall impact resistance, making it a potential application in fields such as protective equipment and composite armor.
[0019] 2) The nanomaterials introduced in this invention have high conductivity and can form a conductive network to improve shielding effectiveness. The nanomaterials are evenly distributed inside the fiber, and compared with traditional surface coating methods, they have a more stable and uniform shielding effect. They can be used in consumer electronics, low-altitude economy and smart textiles and other fields.
[0020] 3) This invention maintains the lightweight characteristics of high-performance fibers through uniform doping of nanomaterials. Compared with traditional coating methods, it does not add extra weight and preserves the original advantages of the fibers. The integrated spinning method avoids the problem of later coating layer peeling, improving durability and service life.
[0021] 4) This invention employs an improved spinning process, enabling large-scale continuous production, improving economic efficiency, and is applicable to traditional textile machinery, facilitating the upgrading of existing production lines. Attached Figure Description
[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0023] Figure 1 This is a comparison diagram of the impact resistance of the modified high-performance fiber woven fabric and the unmodified fiber woven fabric in a typical embodiment of the present invention.
[0024] Figure 2 This is a comparison diagram of the electromagnetic shielding performance of the modified high-performance fiber woven fabric and the unmodified fiber woven fabric in a typical embodiment of the present invention.
[0025] Figure 3 This is a comparison diagram of the electrical conductivity of woven fabrics with different contents of modified high-performance fibers and woven fabrics without modification in a typical embodiment of the present invention.
[0026] Figure 4 This is a microscopic morphology diagram of the modified fiber in a typical embodiment of the present invention;
[0027] Figure 5 This is a microscopic morphology diagram of a modified high-performance fiber braid in a typical embodiment of the present invention;
[0028] Figure 6 This is a macroscopic view of a modified high-performance fiber woven fabric in a typical embodiment of the present invention. Detailed Implementation
[0029] In view of the limitations of existing fiber braided fabrics, the inventors of this invention, through long-term research and extensive practice, have proposed the technical solution of this invention, which mainly provides a method for preparing modified high-performance fiber braided fabrics. This method introduces nanomaterials such as carbon nanotubes during the spinning stage, mixes them with the monomers of high-performance fibers, and then spins them. After processing through a special weaving process, modified high-performance fiber braided fabrics with impact resistance and electromagnetic shielding properties are prepared.
[0030] The following will further explain the technical solution, its implementation process, and its principles. However, it should be understood that within the scope of this invention, the above-mentioned technical features of this invention and the technical features specifically described below (in embodiments) can be combined with each other to form new or preferred technical solutions. Due to space limitations, they will not be described in detail here.
[0031] As one aspect of the technical solution of this invention, a method for preparing a modified high-performance fiber woven fabric includes:
[0032] Nanomaterials used as functional fillers are mixed with high-performance fiber monomers to uniformly disperse the nanomaterials in the high-performance fiber monomers, resulting in a mixture.
[0033] Using the mixture as a spinning solution, modified fibers are prepared by spinning technology, wherein nanomaterials are arranged axially inside the modified fibers.
[0034] The modified fibers are woven using a weaving process to obtain a modified high-performance fiber woven fabric.
[0035] In some embodiments, the nanomaterial is a chemically functionalized nanomaterial. The chemical functionalization includes at least one of carboxylation, amination, etc.
[0036] In some preferred embodiments, the nanomaterials may include one or more of highly conductive and high-strength nanomaterials such as graphene, carbon nanotubes (CNTs), and MXene, but are not limited to these. This invention improves the uniformity and interfacial bonding of the material by chemical functionalization (such as carboxylation and amination) or ultrasonic dispersion, thereby uniformly dispersing the nanomaterials within high-performance fiber monomers.
[0037] Furthermore, taking carbon nanotubes as an example, the specific steps and conditions for their chemical functionalization are as follows: multi-walled or single-walled carbon nanotubes are mixed with concentrated nitric acid, or nitric acid and sulfuric acid are mixed at a volume ratio of 1:3, heated to 60-80°C for 3-8 hours, and ultrasonically stirred for 30-60 minutes. After repeated centrifugation and washing, the pH value is brought close to 7, and finally vacuum dried at 60-80°C for 12-24 hours.
[0038] In some embodiments, the material of the high-performance fiber monomer may include one or more combinations of PBO, aramid, ultra-high molecular weight polyethylene (UHMWPE), etc., but is not limited thereto.
[0039] In some implementation schemes, the preparation method specifically includes:
[0040] Nanomaterials are dispersed in water or a specified organic solvent and then ultrasonically dispersed to form a nanomaterial dispersion.
[0041] High-performance fiber monomers are dissolved in a mixture of a specified organic solvent and a specified salt to form a fiber precursor solution;
[0042] The nanomaterial dispersion and fiber precursor solution are mixed evenly and allowed to stand to remove bubbles, forming a spinning solution.
[0043] In some preferred embodiments, the specified organic solvent may be one or more of N-methylpyrrolidone (NMP), N,N-dimethylacetamide (DMA), N,N-dimethylformamide (DMF), etc., but is not limited thereto.
[0044] In some preferred embodiments, the designated salt may be one or a combination of two of CaCl2, LiCl, etc., but is not limited thereto.
[0045] Furthermore, the mixed system can be a combination of NMP / CaCl2, DMA / LiCl, DMF / LiCl, NMP / LiCl, etc.
[0046] In some preferred embodiments, the ultrasonic dispersion power is 200-500W and the time is 30-60min.
[0047] In some preferred embodiments, the nanomaterial dispersion may also include selectively added or omitted polyvinylpyrrolidone (PVP) to improve stability.
[0048] In some preferred embodiments, the concentration of high-performance fiber monomers in the fiber precursor solution is 12-15 wt%.
[0049] In some preferred embodiments, the nanomaterials in the nanomaterial dispersion account for 0.5–2 wt% of the mass of the fiber precursor solution. This invention improves the electromagnetic shielding capability of modified fibers while ensuring their strength by employing specific nanomaterial doping ratios and distribution methods. Specifically, the nanomaterial doping ratio is controlled at 0.5–2 wt%, preferably 1–2 wt%, to ensure that conductive network construction and enhanced mechanical properties are achieved without affecting spinning continuity and fiber integrity. This process significantly improves the tensile strength and electromagnetic shielding capability of the fibers, achieving a synergistic improvement in mechanical and functional properties.
[0050] In some embodiments, the preparation method specifically includes: using at least one of melt spinning, gel spinning, wet spinning, etc., followed by stretching, heat treatment, and chemical curing to obtain the modified fiber. This invention, by employing the above spinning technology, enables the nanomaterials to be uniformly distributed within the fiber, forming an overall reinforcing effect.
[0051] In some preferred embodiments, when melt spinning is used, polymer masterbatches such as PBO and UHMWPE are doped with nanomaterials, the extrusion zone temperature is controlled at 200-250°C, the spinneret temperature is 210-240°C, the drawing speed is 60-100 m / min, and a multi-hole nozzle with an orifice diameter of 0.2-0.35 mm and an L / D ratio of 3-5 is used.
[0052] In some preferred embodiments, when wet spinning is used, the flow rate of the spinning solution is controlled to be 0.5–1 cc / min, the nozzle orifice diameter is 100–150 μm, the temperature is 20–25 °C, the coagulation bath is a mixture of water and methanol, the temperature of the coagulation bath is 0–10 °C, the draw ratio is 170–200%, and the coagulation length (i.e., the flow distance required for the fiber to complete solvent replacement, desolventization, and solidification in the coagulation bath) is 10–30 cm.
[0053] In some preferred embodiments, when gel spinning is employed, the functionalized nanomaterials are ultrasonically dispersed into the gel solution, stirred at 60°C for 6 hours, with the spinneret temperature controlled at 20–150°C, the spinneret orifice diameter at 0.2–0.5 mm, the spinning speed at 1–10 m / min, and the draw ratio at 5–20. The gel solution is a semi-solid or highly viscous polymer system (polyolefin gel systems: such as ultra-high molecular weight polyethylene; polyamide gel systems: such as nylon; aromatic polyamide gel systems: such as aramid, etc.), existing between a solution and a solid state. It typically possesses a certain structural network, enabling it to flow and form while also having a preliminary internal structure, used to maintain fiber morphology during the drawing process in spinning.
[0054] In some embodiments, the preparation method specifically includes: drawing out the shaped filament bundle obtained after spinning via guide rollers, followed by a first-stage hot drawing treatment, a second-stage hot drawing treatment, and a heat-setting and curing treatment, so that the nanomaterials are axially aligned within the modified fiber. In the spinning process, this invention further improves the mechanical properties and stability of the modified fiber through methods such as drawing, heat treatment, and chemical curing, controlling the orientation of nanomaterials (such as carboxylated CNTs or graphene) within the modified fiber, ensuring their uniform orientation along the fiber axis (due to the template properties of the nanomaterials themselves, the surrounding molecular chains are neatly aligned around them), thereby improving mechanical properties such as electrical conductivity and impact resistance.
[0055] In some preferred embodiments, the stretching ratio of the first stage of hot stretching treatment is 4 to 6, and the temperature is 60 to 100°C.
[0056] In some preferred embodiments, the draw ratio of the two-stage hot drawing process is 8 to 12, and the heat treatment temperature is 100 to 150°C.
[0057] In some preferred embodiments, the temperature of the heat setting and curing treatment is 120-140°C, and the time is 5-15 minutes.
[0058] In some preferred embodiments, the preparation method further includes: drying the obtained modified fiber at a temperature of 50–70°C for 12–24 hours.
[0059] In some implementations, the weaving process may include one or more combinations of weaving techniques such as plain weave, twill weave, satin weave, and three-dimensional weave, thereby improving impact resistance by optimizing the weaving structure.
[0060] Furthermore, in the weaving process, the number of modified fibers in the warp direction is 30-80 strands / 10cm, and the number of modified fibers in the weft direction is 30-70 strands / 10cm.
[0061] This invention can control the density and layering of woven fabrics by adjusting parameters such as the spinneret diameter, draw ratio, and fiber precursor solution concentration. It can also improve the interlayer bonding strength and shielding performance of materials by controlling the number of modified fibers arranged in the warp and weft directions.
[0062] In some preferred embodiments, taking functionalized graphene as an example, a method for preparing a modified high-performance fiber woven fabric includes the following steps:
[0063] I. Graphene Functionalization Process:
[0064] Graphene oxide (GO) was prepared using a modified Hummers process, with raw materials including natural graphite, NaNO3, concentrated sulfuric acid, and KMnO4. Graphene oxide slurry was obtained through a low-temperature oxidation reaction.
[0065] GO was refluxed with a mixture of nitric acid and sulfuric acid (volume ratio 1:3) for 2-4 hours and then carboxylated at 60-70°C to obtain GO-COOH rich in carboxyl groups.
[0066] After repeated washing with deionized water until neutral, the product is vacuum dried at 60–80°C for 12–24 hours to obtain functionalized graphene powder.
[0067] II. Pre-mixing and dispersion steps of the precursor liquid:
[0068] Disperse GO-COOH in water or NMP system at a concentration of 0.5–2 mg / mL, and ultrasonically disperse (200–500 W, 30–60 minutes). If necessary, add polyvinylpyrrolidone (PVP) to improve stability.
[0069] The aramid precursor solution was prepared by dissolving aramid 1313 (PAI) in an NMP and CaCl2 system, with the polymer concentration controlled at 12-15 wt%.
[0070] GO-COOH was added to the aramid precursor solution at a doping ratio of 1 to 2 wt%, and after being magnetically stirred evenly, it was allowed to stand to remove bubbles, thus forming a spinning solution.
[0071] III. Wet spinning forming steps:
[0072] The spinning solution is extruded through a spinneret, with the spinneret orifice diameter controlled at 100–150 μm and the temperature controlled at 20–25 °C.
[0073] The filaments are spun into a coagulation bath (a mixture of deionized water and methanol), with the temperature controlled at 0–10°C and the coagulation length at 10–30 cm.
[0074] The formed filament bundle is drawn out by the guide rollers and enters the primary drawing zone.
[0075] IV. Drawing and heat treatment steps:
[0076] The wet hot stretching ratio is controlled at 4-6, and the temperature is 60-100℃.
[0077] The two-stage hot drawing ratio is 8-12, and the heat treatment temperature is 100-150℃, which is used to improve the molecular chain orientation and the graphene sheet arrangement direction.
[0078] The microstructure is cured by heat setting (temperature 120-140℃, time 5-15 minutes), which improves the mechanical and electrical stability of the fiber.
[0079] The modified fibers are dried (at a temperature of 50–70°C in a vacuum environment for 12–24 hours) and then wound up.
[0080] V. Modified high-performance fiber woven fabrics are produced by using plain weave, twill weave, satin weave, three-dimensional weave, and other weaving techniques.
[0081] As another aspect of the technical solution of the present invention, it also relates to modified high-performance fiber woven fabrics prepared by the aforementioned preparation method.
[0082] As another aspect of the technical solution of the present invention, it also relates to a composite material, which includes: a resin matrix material and the aforementioned modified high-performance fiber woven fabric.
[0083] Furthermore, the resin matrix material may be one or a combination of two of phenolic resin, epoxy resin, etc., but is not limited to this.
[0084] Furthermore, the content of modified high-performance fiber braid in the composite material is 60–85 wt%.
[0085] This invention improves heat resistance and stability by further compounding modified high-performance fiber woven fabrics with matrices such as phenolic resin and epoxy resin.
[0086] As another aspect of the technical solution of the present invention, it also relates to the application of the aforementioned modified high-performance fiber woven fabrics or composite materials.
[0087] Because this invention introduces nanomaterials during the spinning stage, which are then uniformly dispersed within the modified fiber, it enhances the strength, toughness, and elongation at break of the modified fiber, thereby improving its impact resistance. Furthermore, the braided structure design can further absorb impact energy, enhancing the overall impact resistance, and has application potential in fields such as protective equipment and composite armor.
[0088] Furthermore, nanomaterials such as graphene and carbon nanotubes possess high conductivity and can form conductive networks, thereby improving shielding effectiveness. This invention involves thoroughly and uniformly mixing the nanomaterials with high-performance fiber monomers before spinning, rather than through subsequent coating, plating, or impregnation. This results in a uniformly distributed functional filler within the modified fiber, providing a more stable and uniform shielding effect compared to traditional surface coating methods. This material can be used in consumer electronics, low-altitude economy, and smart textiles.
[0089] This invention maintains the lightweight properties of high-performance fibers through uniform doping with nanomaterials, preserving the original advantages of the fibers without adding extra weight compared to traditional coating methods. Furthermore, the integrated spinning method avoids the problem of later-stage coating peeling, improving durability and service life.
[0090] The technical solution of the present invention will be further described in detail below with reference to several preferred embodiments and accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. It should be noted that the following embodiments are intended to facilitate understanding of the present invention, and do not constitute any limitation thereof. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions or according to the conditions recommended by the manufacturer.
[0091] Example 1
[0092] A method for preparing a modified high-performance fiber woven fabric includes the following steps:
[0093] It provides functionalized graphene powder, namely GO-COOH rich in carboxyl groups;
[0094] GO-COOH was dispersed in water at a concentration of 1 mg / mL and ultrasonically dispersed (350 W, 50 minutes).
[0095] The aramid precursor solution was prepared by dissolving aramid 1313 (PAI) in an NMP and CaCl2 system, with the polymer concentration controlled at 12 wt%.
[0096] GO-COOH was added to the aramid precursor solution at a doping ratio of 0.5 wt%, and after being magnetically stirred evenly, it was allowed to stand to remove bubbles, thus forming a spinning solution.
[0097] Wet spinning was used, in which the spinning solution was extruded through a spinneret at a flow rate of 0.8 cc / min, a spinneret orifice diameter of 120 μm, and a temperature of 20 °C. The spinneret was then inserted into a coagulation bath (a mixture of deionized water and methanol) at a temperature of 5 °C, a draw ratio of 180%, and a coagulation length of 10 cm.
[0098] The formed filament bundle is drawn out by guide rollers and enters the stretching zone. The first stage of wet hot stretching has a ratio of 5 and a temperature of 70℃; the second stage of hot stretching has a ratio of 10 and a heat treatment temperature of 130℃. After heat setting at 130℃ for 10 minutes, the resulting modified fiber is vacuum dried at 50℃ for 24 hours and then wound up.
[0099] Modified fibers were woven using three-dimensional weaving to obtain modified high-performance fiber woven fabrics.
[0100] The conductivity of the modified fiber prepared in this embodiment was tested to be 2.2 × 10⁻⁶. 6 The modified high-performance fiber braided fabric produced with S / m has a maximum load of 1900N and an EMI shielding effectiveness of 53dB (X-band).
[0101] Example 2
[0102] A method for preparing a modified high-performance fiber woven fabric includes the following steps:
[0103] We provide functionalized carbon nanotube powder, namely CNT-COOH rich in carboxyl groups;
[0104] CNT-COOH was dispersed in NMP at a concentration of 1 mg / mL and ultrasonically dispersed (350 W, 50 minutes).
[0105] The aramid precursor solution was prepared by dissolving aramid 1313 (PAI) in an NMP and CaCl2 system, with the polymer concentration controlled at 15 wt%.
[0106] CNT-COOH was added to the aramid precursor solution at a doping ratio of 0.5 wt%, and after being magnetically stirred evenly, it was allowed to stand to remove bubbles, thus forming a spinning solution.
[0107] Wet spinning was used, in which the spinning solution was extruded through a spinneret with a spinneret orifice diameter of 120 μm, a flow rate of 0.8 cc / min, and a temperature of 20 °C. The spinneret was then introduced into a coagulation bath (a mixture of deionized water and methanol) at a temperature of 5 °C, a draw ratio of 180%, and a coagulation length of 20 cm.
[0108] The formed filament bundle is drawn out by guide rollers and enters the stretching zone. The first stage of wet hot stretching has a ratio of 5 and a temperature of 70℃; the second stage of hot stretching has a ratio of 10 and a heat treatment temperature of 130℃. After heat setting at 130℃ for 10 minutes, the resulting modified fiber is vacuum dried at 70℃ for 12 hours and then wound up.
[0109] Modified fibers were woven using three-dimensional weaving to obtain modified high-performance fiber woven fabrics.
[0110] The conductivity of the modified fiber prepared in this embodiment was tested to be 2 × 10⁻⁶. 6 The modified high-performance fiber braided fabric produced with S / m has a maximum load of 1500N and an EMI shielding effectiveness of 45dB (X-band).
[0111] Example 3
[0112] A method for preparing a modified high-performance fiber woven fabric includes the following steps:
[0113] It provides functionalized graphene powder, namely GO-COOH rich in carboxyl groups;
[0114] GO-COOH was dispersed in NMP at a concentration of 1 mg / mL and ultrasonically dispersed (350 W, 50 minutes).
[0115] The aramid precursor solution was prepared by dissolving aramid 1313 (PAI) in an NMP and CaCl2 system, with the polymer concentration controlled at 13 wt%.
[0116] GO-COOH was added to the aramid precursor solution at a doping ratio of 2wt%, and after being magnetically stirred evenly, it was allowed to stand to remove bubbles, thus forming a spinning solution.
[0117] Wet spinning was used, in which the spinning solution was extruded through a spinneret with a spinneret orifice diameter of 120 μm, a flow rate of 0.8 cc / min, and a temperature of 20 °C. The spinneret was then introduced into a coagulation bath (a mixture of deionized water and methanol) at a temperature of 5 °C, a draw ratio of 180%, and a coagulation length of 30 cm.
[0118] The formed filament bundle is drawn out by guide rollers and enters the drawing zone. The first stage of wet hot drawing has a ratio of 5 and a temperature of 70℃; the second stage of hot drawing has a ratio of 10 and a heat treatment temperature of 130℃. After heat setting at 130℃ for 10 minutes, the modified fiber is vacuum dried at 60℃ for 18 hours and then wound up.
[0119] Modified fibers were woven using three-dimensional weaving to obtain modified high-performance fiber woven fabrics.
[0120] The conductivity of the modified fiber obtained in this embodiment was tested to be 1.7 × 10⁻⁶. 6 The modified high-performance fiber braided fabric produced with S / m has a maximum load of 1500N and an EMI shielding effectiveness of 50dB (X-band).
[0121] Example 4
[0122] MXene was dispersed in deionized water at a concentration of 1 mg / mL, and 0.8 wt% polyvinylpyrrolidone (PVP) was added to improve stability. The mixture was then ultrasonically dispersed (300 W, 40 minutes).
[0123] The aramid precursor solution was prepared by dissolving aramid 1313 (PAI) in an NMP and LiCl system, with the polymer concentration controlled at 12 wt%.
[0124] Functionalized MXene was added to the aramid precursor solution at a doping ratio of 1 wt%, and after mechanical stirring (400 rpm) for 1 hour, it was allowed to stand to degas, forming a spinning solution.
[0125] Wet spinning was used, in which the spinning solution was extruded through a spinneret with a spinneret orifice diameter of 120 μm, a flow rate of 1.0 cc / min, and a temperature of 20 °C. The spinneret was then placed into a coagulation bath (deionized water / methanol mass ratio 1:1) at a temperature of 10 °C, a draw ratio of 170%, and a coagulation length of 10 cm.
[0126] The formed filament bundle is drawn out by guide rollers and enters the drawing zone. The first stage of wet hot drawing has a ratio of 4 and a temperature of 70℃; the second stage of hot drawing has a ratio of 8 and a heat treatment temperature of 120℃. After heat setting at 120℃ for 10 minutes, the modified fiber is vacuum dried at 50℃ for 24 hours and then wound up.
[0127] MXene composite modified fibers were woven using three-dimensional weaving to obtain modified high-performance fiber woven fabrics.
[0128] The volumetric conductivity of the MXene-modified fiber prepared in this embodiment was tested to be 3.5 × 10⁻⁶. 6 The modified high-performance fiber braided fabric produced with S / m has a maximum load of 1700N and an EMI shielding effectiveness of 51dB (X-band).
[0129] Example 5
[0130] A method for preparing a modified high-performance fiber woven fabric includes the following steps:
[0131] It provides functionalized graphene powder, namely GO-COOH rich in carboxyl groups;
[0132] GO-COOH was dispersed in NMP at a concentration of 1 mg / mL and ultrasonically dispersed (350 W, 50 minutes).
[0133] The fiber precursor solution uses poly(p-phenylenebenzodiazole) (PBO) dissolved in a polyphosphoric acid (PPA) system, with the polymer concentration controlled at 15 wt%.
[0134] GO-COOH was added to the PBO precursor solution at a doping ratio of 1 wt%, and after being magnetically stirred evenly, it was allowed to stand to remove bubbles, thus forming a spinning solution.
[0135] The dry-jet wet spinning method is adopted. The spinning solution is extruded through the spinneret with a spinneret orifice diameter of 150μm, a flow rate of 0.5cc / min, and a temperature of 25℃. The spinneret first passes through an air layer and then enters a coagulation bath (formamide) with a temperature of 0℃, a draw ratio of 180%, and a coagulation length of 15cm.
[0136] The formed filament bundle is drawn out by guide rollers and enters the drawing zone. The first wet drawing ratio is 4 and the temperature is 80℃; the second hot drawing ratio is 8 and the heat treatment temperature is 150℃. After heat setting at 150℃ for 15 minutes, the modified fiber is vacuum dried at 60℃ for 24 hours and then wound up.
[0137] Modified PBO fibers were woven using three-dimensional weaving to obtain modified high-performance fiber woven fabrics.
[0138] Tests showed that the PBO modified fiber obtained in this embodiment has a strength of 5.8 GPa, the maximum load of the modified high-performance fiber woven fabric is 1900 N, and the EMI shielding effectiveness is 48 dB (X-band).
[0139] Example 6
[0140] A method for preparing a modified high-performance fiber woven fabric includes the following steps:
[0141] It provides functionalized graphene powder, namely GO-COOH rich in carboxyl groups;
[0142] GO-COOH was dispersed in paraffin oil at a concentration of 1 mg / mL and ultrasonically dispersed (300 W, 40 minutes).
[0143] The fiber precursor solution is made by dissolving ultra-high molecular weight polyethylene (UHMWPE) in a paraffin oil and white oil system, with the polymer concentration controlled at 12wt%.
[0144] GO-COOH was added to the UHMWPE precursor solution at a doping ratio of 0.8 wt%, and after being magnetically stirred evenly, it was allowed to stand to remove bubbles, forming a gel spinning solution.
[0145] The gel spinning process was adopted, in which the spinning solution was extruded through a spinneret with a spinneret orifice diameter of 220 μm and a temperature of 25℃; the spinneret was then placed into a coagulation bath (ethanol) with a coagulation length of 10 cm, a spinning speed of 5 m / min, and a draw ratio of 10.
[0146] The formed filament bundle is drawn out by guide rollers and enters the stretching zone. The first stage of wet hot stretching has a ratio of 5 and a temperature of 70℃; the second stage of hot stretching has a ratio of 12 and a heat treatment temperature of 140℃. After heat setting at 140℃ for 15 minutes, the modified fiber is vacuum dried at 50℃ for 24 hours and then wound up.
[0147] Modified UHMWPE fibers were woven using three-dimensional weaving to obtain modified high-performance fiber woven fabrics.
[0148] Tests showed that the UHMWPE modified fiber obtained in this embodiment has a strength of 3.5 GPa, the maximum load of the modified high-performance fiber woven fabric is 1600 N, and the EMI shielding effectiveness is 45 dB (X-band).
[0149] Example 7
[0150] A method for preparing a modified high-performance fiber woven fabric includes the following steps:
[0151] It provides functionalized graphene powder, namely GO-COOH rich in carboxyl groups;
[0152] GO-COOH was dispersed in a polyacrylate (PAA) solution at a concentration of 0.8 mg / mL, ultrasonically dispersed (500 W, 30 min), then centrifuged, washed and dried to obtain dry dispersed GO-COOH powder;
[0153] Polyethylene terephthalate (PET) was selected as the base resin. During the mixing and extrusion process, GO-COOH was uniformly mixed with PET particles at a doping ratio of 0.5 wt%, and then melt-blended in a twin-screw extruder at a temperature range of 260–280 °C to obtain a GO / PET blend melt.
[0154] The above GO / PET blend was cooled and cut into spinning chips;
[0155] The spun fibers are heated to 275°C and uniformly melted using a melt spinning device. The fibers are then extruded through a spinneret with a spinneret orifice diameter of 200 μm, an L / D ratio of 3, a spinneret temperature of 220°C, a drawing speed of 80 m / min, and a cooling air temperature of 20°C. After cooling and setting, nascent fibers are formed.
[0156] The nascent fiber was subjected to a first stage of hot stretching with a ratio of 4 (100℃) and a second stage of hot stretching with a ratio of 8 (130℃), and finally heat-set at 140℃ for 10 minutes to obtain GO / PET modified fiber.
[0157] Modified fibers were woven using a three-dimensional weaving process to obtain modified high-performance fiber woven fabrics.
[0158] Performance testing showed that the electrical conductivity of the GO / PET modified fiber prepared in this embodiment was 1.1 × 10⁻⁶. 5 The modified high-performance fiber woven fabric produced with an S / m ratio has a maximum load of 1450N and an electromagnetic shielding effectiveness of 52dB (X-band).
[0159] Example 8
[0160] A method for preparing a modified high-performance fiber woven fabric includes the following steps:
[0161] It provides functionalized graphene powder, namely GO-COOH rich in carboxyl groups;
[0162] GO-COOH was dispersed in paraffin oil at a concentration of 1 mg / mL and ultrasonically dispersed (200 W, 60 minutes).
[0163] The fiber precursor solution is made by dissolving ultra-high molecular weight polyethylene (UHMWPE) in a paraffin oil and white oil system, with the polymer concentration controlled at 10 wt%.
[0164] GO-COOH was added to the UHMWPE precursor solution at a doping ratio of 1 wt%, and after being magnetically stirred evenly, the solution was cooled at low temperature to form a high-viscosity gel-like spinning solution.
[0165] The gel spinning method was used, in which the gel spinning solution was extruded through a spinneret with a spinneret orifice diameter of 120 μm and an extrusion temperature of 25 °C. After the spinneret was cooled in air, it was placed in a coagulation bath (ethanol) at a temperature of 10 °C and a coagulation length of 10 cm.
[0166] The nascent gel fibers are drawn out by guide rollers and enter the stretching zone. One stage involves a wet stretching ratio of 6 and a temperature of 60℃; the second stage involves a hot stretching ratio of 12, a heat treatment temperature of 150℃, and heat setting at 140℃ for 5 minutes.
[0167] The prepared GO / UHMWPE gel fibers were vacuum dried at 70°C for 12 hours and then wound up.
[0168] Modified fibers were woven using three-dimensional weaving to obtain modified high-performance fiber woven fabrics.
[0169] The gel-spun modified fiber obtained in this embodiment has a strength of 3.4 GPa and an electrical conductivity of 2.8 × 10⁻⁶. 6 The modified high-performance fiber braided fabric produced has a maximum load of 1750N and an EMI shielding effectiveness of 55dB (X-band) with a strength of S / m.
[0170] Compare with Example 1
[0171] The difference between this comparative example and Example 1 is that no GO-COOH was added to the aramid precursor solution, i.e., the doping ratio was 0 wt%.
[0172] The conductivity of the fiber obtained in this comparative example is 0.1 × 10⁻⁶. 6 With an S / m, the maximum load of the resulting fiber braided fabric is 1300N, and the EMI shielding effectiveness is 40dB (X-band).
[0173] Compare with Example 2
[0174] A graphene solution with a mass fraction of 10 wt% was directly coated onto an aramid plain weave fabric.
[0175] The maximum load of the fiber braided fabric obtained in this comparative example is 1200N, and the EMI shielding effectiveness is 50dB (X-band).
[0176] like Figure 1 The image shows a comparison of the impact resistance of a modified high-performance fiber woven fabric obtained in a typical embodiment with that of a woven fabric without modification. Figure 2 A comparison of the electromagnetic shielding performance of the modified high-performance fiber woven fabric and the unmodified fiber woven fabric; Figure 3 This is a comparison chart showing the electrical conductivity of woven fabrics with different contents of modified high-performance fibers and woven fabrics without modification.
[0177] Figure 4 This is a microscopic morphology image of the modified fibers obtained in a typical embodiment. Figure 5 This is a microscopic morphology image of the modified high-performance fiber braid obtained in a typical embodiment. The macroscopic image is shown below. Figure 6 As shown.
[0178] In addition, the inventors of this case also conducted experiments with other raw materials, process operations, and process conditions described in this specification, referring to the aforementioned embodiments, and obtained relatively ideal results in all cases.
[0179] The above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing a modified high-performance fiber woven fabric, characterized in that, include: Nanomaterials used as functional fillers are mixed with high-performance fiber monomers to uniformly disperse the nanomaterials in the high-performance fiber monomers, resulting in a mixture. Using the mixture as a spinning solution, modified fibers are prepared by spinning technology, wherein nanomaterials are arranged axially inside the modified fibers. The modified fibers are woven using a weaving process to obtain a modified high-performance fiber woven fabric.
2. The preparation method according to claim 1, characterized in that: The nanomaterial is a chemically functionalized nanomaterial; preferably, the nanomaterial includes one or more of graphene, carbon nanotubes, and MXene. Preferably, the chemical functionalization includes at least one of carboxylation and amination; And / or, the material of the high-performance fiber monomer includes one or more combinations of PBO, aramid, and ultra-high molecular weight polyethylene.
3. The preparation method according to claim 1, characterized in that, include: Nanomaterials are dispersed in water or a specified organic solvent and then ultrasonically dispersed to form a nanomaterial dispersion. High-performance fiber monomers are dissolved in a mixture of a specified organic solvent and a specified salt to form a fiber precursor solution; The nanomaterial dispersion and fiber precursor solution are mixed evenly and allowed to stand to remove bubbles, forming a spinning solution.
4. The preparation method according to claim 3, characterized in that: The specified organic solvent includes one or more combinations of N-methylpyrrolidone, N,N-dimethylacetamide, and N,N-dimethylformamide; And / or, the specified salt includes one or a combination of two of CaCl2 and LiCl; And / or, the ultrasonic dispersion power is 200-500W, and the time is 30-60min; And / or, the nanomaterial dispersion may also include selectively added or omitted polyvinylpyrrolidone; And / or, the concentration of high-performance fiber monomers in the fiber precursor solution is 12-15 wt%; And / or, the nanomaterials in the nanomaterial dispersion account for 0.5 to 2 wt% of the mass of the fiber precursor solution, preferably 1 to 2 wt%.
5. The preparation method according to claim 1, characterized in that, include: The modified fiber is prepared by at least one of melt spinning, gel spinning, and wet spinning, followed by stretching, heat treatment, and chemical curing. Preferably, when melt spinning is used, the temperature of the extrusion zone is controlled at 200-250°C, the temperature of the spinneret is controlled at 210-240°C, the drawing speed is controlled at 60-100 m / min, and a multi-hole nozzle is used with an orifice diameter of 0.2-0.35 mm and an L / D ratio of 3-5. Preferably, when wet spinning is used, the flow rate of the spinning solution is controlled to be 0.5-1 cc / min, the nozzle orifice diameter is 100-150 μm, the temperature is 20-25℃, the coagulation bath is a mixture of water and methanol, the temperature of the coagulation bath is 0-10℃, the draw ratio is 170-200%, and the coagulation length is 10-30 cm. Preferably, when gel spinning is used, the temperature of the spinning head is controlled at 20-150°C, the spinneret diameter is 0.2-0.5 mm, the spinning speed is 1-10 m / min, and the draw ratio is 5-20.
6. The preparation method according to claim 5, characterized in that, include: The shaped filaments obtained after spinning are drawn out by guide rollers, and then subjected to a first-stage hot stretching treatment, a second-stage hot stretching treatment, and a heat setting and curing treatment, so that the nanomaterials are arranged axially inside the modified fiber. Preferably, the draw ratio of the first stage of hot drawing treatment is 4 to 6, and the temperature is 60 to 100°C; Preferably, the draw ratio of the two-stage hot drawing process is 8 to 12, and the heat treatment temperature is 100 to 150°C. Preferably, the temperature for the heat setting and curing treatment is 120–140°C, and the time is 5–15 min; Preferably, the preparation method further includes: drying the obtained modified fiber at a temperature of 50-70°C for 12-24 hours; And / or, the weaving process includes one or more combinations of plain weave, twill weave, satin weave, and three-dimensional weave; preferably, in the weaving process, the modified fibers in the warp direction are 30-80 strands / 10cm, and the modified fibers in the weft direction are 30-70 strands / 10cm.
7. A modified high-performance fiber woven fabric prepared by any one of claims 1-6.
8. A composite material, characterized in that, include: The resin matrix material and the modified high-performance fiber braid as described in claim 7.
9. The composite material according to claim 8, characterized in that: The resin matrix material includes one or a combination of two of phenolic resin and epoxy resin; and / or, the content of modified high-performance fiber braid in the composite material is 60-85 wt%.
10. The application of the modified high-performance fiber woven fabric of claim 7 or the composite material of any one of claims 8-9 in the fields of protective equipment, composite armor, consumer electronics, low-altitude economy or smart textiles.